Why political liberalism? on John Rawls's political turn - Weithman, Paul J., 1959- (New York ; Oxford : Oxford University Press, 2011)
In this work, Paul Weithman offers a fresh, rigorous and compelling interpretation of John Rawls' reasons for taking his so-called 'political turn'.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Rawls, John, -- 1921-2002 -- Criticism and interpretation; Justice; Liberalism; Political stability